Collecting Robert G. Cooper's Articles as Author or Co‐Author From The Journal of Product Innovation Management 1984–2016. Issue 3 (1st March 2017) - Unknown
Abstract : See virtual issue: Collecting Robert G. Cooper's Articles as Author or Co‐Author from the Journal of Product Innovation Management, 1984–2016